BARIERE ÎN CALEA TRANSFORMĂRII REPREZENTĂRII SOCIALE. CUADRINOMUL LUI A. GUSKIN - USM ADMIN (Moldova State University, 2008)
Individuals are characterized by the wish for maintaining existent stereotypes, beliefs and/or representations. In the great majority of cases, they fear their transformation. The wish for permanence, the aim of self-preservation which ensures the identity and the sense prove to be, once again, much more powerful than the spirit of mobility, the orientation towards innovation, the need of change. Why does this happen? What are the social representations' motives in rejecting the idea of transformation? How can be presented the exact name of the levers through which shows the non-wish to keep abreast of the natural way of things, to face new challenges of time, to accept less common «reading grids of reality»? A possible answer to the questions above can be found at A. Guskin, a renowned American psycho sociologist, who identifies eight causes of rejection of the modifications that appear at the level of social cognitions - the sense of competition and of vanity, authoritarianism and dogmatism, the feeling of threatening and fear, prophecies that are fulfilled by themselves (Prophéties que s'accomplissent d'elles-mêmes).